A standardized surgical technique for rat superior cervical ganglionectomy - Savastano, Luis Emilio (2010)
Superior cervical ganglionectomy (SCGx) is a valuable microsurgical model to study the role of the sympathetic nervous system in a vast array of physiological and pathological processes, including homeostatic regulation, circadian biology and the dynamics of neuronal dysfunction and recovery after injury. Despite having several experimental applications in the rat, a thorough description of a standardized procedure has never been published. Here, we provide a brief review of the principal features and experimental uses of the SCGx, the surgical anatomy of the neck and sympathetic cervical chain, and a step-by-stepdescription of how to consistently remove the superior cervical ganglia through the omohyoid muscle or the carotid triangle. Furthermore, we suggest procedures and precautions to be taken during and aftersurgery to optimize results and describe tools to validate surgical success. We expect that the following standardized and optimized protocol will allow researchers to organize knowledge into a cohesive framework in those areas where the SCGx is applied.